Pengembangan Worksheet Berbasis Modified Inquiry Pada Science Studio for Physics Jeulin - Dian Pertiwi Rasmi; Agus Setyo Budi; I Made Astra (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The purpose of this research is the development of a worksheet based on the inqury modified for undergraduate students. The methodology of this research is the development of research and literature review.The development model used in this study is the Borg and Gall which comprises: a preliminary study, planning model development, validation, evaluation, revision and implementation. The instrument used in this study is a questionnare. Validation is done by physics experts and media experts. The validity results was calculated by using the formula Product Moment, while reliability is calculated by the formula KR-20. Development of Modified-based worksheet inquiry, the first step is the needs analysis, select the model and suitable material for manufacturing the worksheet, worksheet development process, develop instruments validation to see compatibility materials and media effectiveness worksheet and tested.Keywords: Worksheet Modified Inquiry, Development Worksheet